Role of perilipin 2 in microvascular obstruction in patients with ST-elevation myocardial infarction. Issue 6 (2nd October 2020) - Russo, Michele; Montone, Rocco A; D'Amario, Domenico; Camilli, Massimiliano; Canonico, Francesco; Santamaria, Claudia; Iannaccone, Giulia; Pedicino, Daniela; Pidone, Chiara; Galli, Mattia; Trani, Carlo; Severino, Anna; et al.
Abstract: Aims: Coronary microvascular obstruction (MVO) occurs frequently in patients with ST-elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI). However, mechanisms are multiple and not yet fully understood. Perilipin 2 (PLIN2) is involved in lipid metabolism of macrophages resident in atherosclerotic plaques, along with a role in enhancing plaque inflammation. We studied the association between PLIN2 and MVO in STEMI patients undergoing primary PCI, and we assessed the role of PLIN2 to predict major adverse cardiovascular events (MACEs). Methods and results: STEMI patients undergoing primary PCI were enrolled. PLIN2 was evaluated in peripheral blood monocytes; MVO was assessed using coronary angiogram. MACEs, as a composite of cardiac death, non-fatal myocardial infarction, re-admission for heart failure, and target vessel revascularization were investigated at follow-up. Among 100 STEMI patients, 33 (33.0%) had MVO. Patients with MVO had higher levels of PLIN2 (1.03 ± 0.28 vs. 0.90 ± 0.16, P = 0.019). Age [odds ratio (OR) (95% confidence interval, CI), 1.045 (1.005–1.087), P = 0.026] and PLIN2 [OR (95% CI), 16.606 (2.027–136.030), P = 0.009] were associated with MVO at univariate analysis, although only PLIN2 [OR (95% CI), 12.325 (1.446–105.039), P = 0.022] was associated with MVO at multivariate analysis. After a mean follow-up of 182.2 ± 126.6 days, 13 MACEs occurred. MVO [hazard ratio (HR) (95% CI), 6.791 (2.053–22.462), P = 0.002], hypercholesterolaemia [HR (95% CI), 3.563 (1.094–11.599), P = 0.035], and PLIN2 [HR (95% CI), 82.991 (9.857–698.746), P < 0.001] were predictors of MACEs at univariate analysis, although only PLIN2 [HR (95% CI), 26.904 (2.461–294.100), P = 0.007] predicted MACEs at multivariate analysis. Conclusions: In STEMI patients undergoing primary PCI, PLIN2 was independently associated with MVO and was an independent predictor of MACEs at follow-up, suggesting to further explore PLIN2 as a target for future cardioprotection therapies.